2017
DOI: 10.1016/j.enbuild.2016.12.085
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of the Trombe wall temperature fluctuations for high range climate conditions: Influence of ventilation openings and shading devices

Abstract: a b s t r a c tDespite the studies already developed about Trombe walls, more research work is needed to contribute to the knowledge about their behaviour and optimize it according to the specific characteristics of each climatic region. The ventilation openings and the shading device operation decisively influence the temperatures fluctuation along the system and that impact should be discussed.In this context, a test cell with a classical Trombe wall was submitted to real climatic conditions in a Portuguese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…The methodology described above was applied to a Trombe wall that integrates the envelope of a building located in a Portuguese city characterized by high thermal amplitudes during the day and along the year (Briga Sá et al, 2017). The constructive details of the studied Trombe wall system will be presented in the next section.…”
Section: Trombe Wall Thermal Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The methodology described above was applied to a Trombe wall that integrates the envelope of a building located in a Portuguese city characterized by high thermal amplitudes during the day and along the year (Briga Sá et al, 2017). The constructive details of the studied Trombe wall system will be presented in the next section.…”
Section: Trombe Wall Thermal Performancementioning
confidence: 99%
“…The ventilation system has a fundamental role in the Trombe wall system performance. Briga Sá et al (2017) developed research work about the classical Trombe wall thermal performance based on the experimental analysis of the system under real weather conditions. The influence of the ventilation system on the Trombe wall thermal performance was analysed, and the results showed that opening or closing the air vents decisively influences the air layer and the massive wall temperature fluctuation and consequently the temperature inside the room.…”
Section: Introductionmentioning
confidence: 99%
“…However, they require highly specialized knowledge of numerical modelling, building physics and thermodynamics. In the evaluation of the thermal efficiency of prototypes the validation of numerical models is strongly supported by the data obtained from experimental tests performed on physical models in natural [26] or laboratory conditions [27]. The evaluation of the thermal efficiency of the IGW presented in the paper was based on the analysis of the data obtained in the field tests on the IGW using a test chamber of controlled indoor temperature.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is the fact that construction practices differ significantly from country to country, so building design strategies should take into account significant regional differences in climate patterns [17]. Therefore, despite the numerous studies already carried out on solar walls, more work needs to be done to gain knowledge about their behavior and to optimize them according to the specificity of each climate region [29].…”
Section: Introductionmentioning
confidence: 99%